The Influence of the Symbols of Virtue on Maturity in The Alchemist - Dara Alinda; Wahyuni Wahyuni; Adi Prautomo (Faculty of Letters Universitas Balikpapan, 2021)
A virtue is trait of mind and character that help people achieve a good life and sometimes a virtue can be found in the symbols. The symbols of the virtue can have an effect on a person’s maturity in thinking and acting. The theory used in this research is the semiotics approach by using theory of Charles Sanders Peirce about triangle theory, there are representamen or sign, object and interpretant. The methodology used in this study is descriptive qualitative research to explain the data, because the data are analyzed in the form of words and sentences. The data are taken from the sentences and the conversation in the text in The Alchemist by Paulo Coelho. The result of this research is the researcher found the symbols of the virtue such as six of the character symbols and one the object symbols. The symbols are explained with the process of semiotic theory called triadic process, from this process the researcher can determines the maturity of the main character based on seven criteria of maturity.